2012
DOI: 10.1016/j.oooo.2012.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Oral health of the elderly with Alzheimer's disease

Abstract: Elderly subjects with AD had poorer oral health than those without the disease. Despite the positive self-perception of their oral health, the oral health of subjects with AD tended to decline as their disease progressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
1
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 28 publications
8
81
1
8
Order By: Relevance
“…The DMFT index (Table 10) was 19.7 to 26.1 in people without dementia [5, 42], and 14.9 to 28.0 [48, 49] in people with dementia. The lowest DMFT was 14.9, which was derived from a cross-sectional study from Thailand examining older people with dementia without using a control group [49].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The DMFT index (Table 10) was 19.7 to 26.1 in people without dementia [5, 42], and 14.9 to 28.0 [48, 49] in people with dementia. The lowest DMFT was 14.9, which was derived from a cross-sectional study from Thailand examining older people with dementia without using a control group [49].…”
Section: Resultsmentioning
confidence: 99%
“…The lowest DMFT was 14.9, which was derived from a cross-sectional study from Thailand examining older people with dementia without using a control group [49]. Only five studies compared older people with and without dementia, and just one study found a significant difference between the two groups; DMFT 25.5 in people without and DMFT 28.0 in people with dementia [48]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations